Diksi, Gaya Bahasa, dan Citraan dalam Cerkak Pacarku Aneh Karya Lina Maisaroh (Kajian Stilistika) - Farazila, Nurya (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
This study discusses diction, language style, and imagery in a story entitled â€œPacarku Anehâ€ by Lina Maisaroh. The theory used is a stylistic study. The purpose of this study is to: describe the diction, style, and imagery contained in the cerkak. The method used in this study is a qualitative descriptive method, with the analysis technique carried out as reading and understanding the contents of the ingenuity. The research data is in the form of a short text sourced from the kompasiana web published in 2021 with the theme of love. The data collection technique used is a reading and recording technique. Data analysis techniques use interactive descriptive techniques that include data reduction, data classification, and conclusion. The result of this study is in a story entitled My Strange Boyfriend by Lina Maisaroh using denotative diction, connotative diction, auditory imagery, visual imagery, motion imagery, allegory language style, and affirmative language style.